Council-Based Approaches to Reforming the Health Care Response to Domestic Violence: Promising Findings and Cautionary Tales. - Allen, Nicole E.; Larsen, Sadie E.; Javdani, Shabnam; Lehrner, Amy L. (American Journal of Community Psychology, 2012)
Councils are commonly formed to address social issues including intimate partner violence (IPV). Research suggests that councils may be well positioned to achieve proximal outcomes, but that their success may depend on contextual factors. The current study compared providers and health care settings at two points in time to explore the degree to which the Health Care Council achieved proximal outcomes in the health care response to IPV, including: (a) providers' reported capacity to screen for IPV, (b) providers' beliefs about IPV as a health care issue and about the IPV screening process, (c) providers' screening behaviors and (d) organizational policies and protocols to encourage screening. This study, while preliminary, provides support for council-based efforts to stimulate change in the health care response to IPV and also highlights the central role that organizational environment plays in shaping desired outcomes.